HUBUNGAN PENGGUNAAN SITUS JEJARING SOSIAL DAN KONTROL DIRI DENGAN PERILAKU PROSOSIAL REMAJA - Dedy Susanto; Rini Sugiarti (Jurnal Psimawa, 2024)
This research held to search the correlation between usage of social media and self control to prosocial behavior in adolescent. Research method used is quantitative research. Collected 250 respondents filling the questionnaire broadcasted in the twitter with likert scale. Collected data analyzed with Bivariate Analysis and Double Correlation with Statistical Package for Social Sciences 22.0 for windows. Resulting in positive correlation with significant score between the usage of social media and prosocial behavior with r = 0,644 and r² = 0,415. Self control correlated positively and significant to prosocial behaviour with r = 0,673 and r² = 0,453. Finally, the usage of sosial media and self control correlated positively and significant to prosocial behaviour with r = 0,673 and r² = 0,453. This research concludes that there is a positive correlation between the usage of social media and self control with prosocial behaviour.